CLINICAL AND MORPHOLOGICAL DIAGNOSTIC INTRAHEPATIC BILE DUCTS PAUCITY - O. E. Iryshkin; I. M. Iljinsky; O. M. Tsirulnikova; S. V. Gautier (Вестник трансплантологии и искусственных органов, 2013)
Aim. To study the clinica-morphological features of syndromatic and nonsyndromatic paucity of intrahepatic bile ducts in pediatric liver transplant recipients. Methods and results. The clinical records were analyzed and histological studies of native livers of 20 children, who had suffered from paucity of intrahepatic bile ducts and to whom liver transplantation were made, were completed. The obtained data indicate higher levels of AST in patients with nonsyndromatic paucity of intrahepaticbile ducts (p = 0,023). Ductopenia was the more frequent indication of syndromatic form of paucity of intrahepatic bile ducts (p = 0,01), while ductular proliferations, which form «ductular structure», were discovered more often in nonsyndromatic paucity of intrahepaticbile ducts (p = 0,03). The extent of inflammatory-destructive changes was more expressed in nonsyndromatic pauci- ty of intrahepatic bile ducts (p = 0,01). Fibrosis or cirrhosis was formed more often in nonsyndromatic paucity of intrahepatic bile ducts (p = 0,008). Conclusion. Our results indicate more severe clinical and morphological manifestations in nonsyndromatic paucity of intrahepatic bile ducts. These findings may suggest about heavier liver condition in patient with nonsyndromatic form of paucity of intrahepatic bile ducts.